Kinetics of cross-linking and de-cross-linking of EPM rubber with thermoreversible Diels-Alder chemistry. (May 2017) - Polgar, L.M.; Kingma, A.; Roelfs, M.; van Essen, M.; van Duin, M.; Picchioni, F.
Graphical abstract: Highlights: (de-)cross-linking kinetics is determined using a unique combination of experiments. A new model for (retro) Diels-Alder reactions kinetics as function of temperature. Equilibrium (de-)cross-linking on the basis of relatively simple kinetics equations. Abstract: The kinetics of the Diels-Alder (DA) cross-linking and retro-Diels-Alder (rDA) de-cross-linking reactions have been studied for furan-containing EPM rubber thermoversibly cross-linked with a bismaleimide. Cross-linking conversions obtained from spectroscopic methods deviate from rheological methods as the former take into consideration both the intermediate DA adduct and complete cross-links, while the latter only determine the formation and decomposition of complete cross-links. The thermoreversibility of the system was shown by a combination of equilibrium swelling and rheological measurements. Dynamic time sweeps of the rubber at different temperatures were used to determine the Arrhenius activation energies of 7.04 and 57.9 kJ/mol for the DA and the rDA reactions, respectively. Ea, DA is relatively low and suggests a diffusion limitation while Ea, rDA correspond to values reported in literature. Both values were used to simulate cross-link density profiles as a function of time and temperature that correspond well with the experimental data.